Gianni Schicchi Polymorphous: Michieletto’s Experiments Between Opera and Cinema (Altre Modernità, 2025)
Due to its inherently heterogeneous nature, the operatic repertoire has long served as a fertile ground for innovation, particularly in the age of media. Traditional media platforms such as cinema, radio, and television swiftly integrated operatic works into their formats, tailoring them to their respective audiences and objectives. This integration gave rise to a variety of hybrid forms, including radio dramas, silent short films, film-operas, and TV-operas, which have proliferated from the early 20th century to the present day. Concurrently, there has been a continuous evolution in opera staging, characterized by a reinterpretation of operatic masterpieces. This study aims to examine two artistic endeavors by Venetian opera director Damiano Michieletto, namely an opera production and an opera-film adaptation, both centered on Gianni Schicchi, the renowned one-act opera from Puccini’s Trittico with a libretto by Giovacchino Forzano (1918). Michieletto’s acclaimed opera production premiered in 2012 at the Austrian Theater an der Wien before being staged in Italy several years later. The opera-film Gianni Schicchi, a collaboration between Michieletto, Genoma Films and Rai Cinema, was presented out of competition at the 39th Turin Film Festival in 2021. This contribution seeks to explore two main aspects: firstly, to analyze the aesthetic and dramaturgical implications of integrating opera into various media platforms; and secondly, to elucidate the stylistic prowess of Damiano Michieletto, a director renowned both in Italy and abroad.
Keywords: Contemporary opera staging; film opera; Damiano Michieletto; Gianni Schicchi; media